TRANSPARANSI PROGRAM BANTUAN LANGSUNG TUNAI DANA DESA DALAM PENANGGULANGAN WABAH COVID-19 DI DESA JENETALLASA KECAMATAN PALLANGGA KABUPATEN GOWA - Riskasari, Riskasari; Ma'ruf, Adnan; Muhiddin, Amir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aims to determine the Transparency of the Village Fund Direct Cash Assistance Program in Combating the Covid-19 Outbreak in Jenetallasa Village, Pallangga District, Gowa Regency. The type of research used is qualitative research methods and descriptive research types. The results of the study consist of four indicators, namely (1) Availability and accessibility of BLT-DD management documents, the community has not had access to obtain information related to important points in BLT-DD management. (2) Clarity and completeness of information on BLT-DD management, the public did not receive clear information about BLT-DD because of the representation of RT heads in the preparation of BLT-DD. (3) Openness of the BLT-DD management process, the village government has billboards and information boards and cooperates with the head of the RT in conveying BLT-DD information to the community. (4) Regulations that guarantee transparency of BLT-DD management, the regulatory framework used by the village government is regulation from the center and has been specified in the regent's rules, but there is no separate regulation from the village government regarding transparency of BLT-DD management in Jenetallasa Village.